Hepatitis B virus infection among children aged 1– 5 years of Mayurbhanj district (Odisha), India: A prospective study protocol - K. Divyasree Bhat; Haimanti Bhattacharya; Yuvaraj Jayaraman; Srikanta Kanungo; Matrujyoti Pattnaik; Sanghamitra Pati; Debdutta Bhattacharya (PLoS ONE, 2025)
Background Over past few years, global healthcare landscape has seen an increased recognition of the significance of infectious diseases, especially those affecting vulnerable populations such as young children, one of these diseases, Hepatitis B has emerged as a notable public health concern. Hepatitis B is highly transmissible during early years of life and may lead to complications like long-term chronicity, cirrhosis of liver and the progression of hepatocellular carcinoma. To address this growing concern, there is a pressing need for community-based studies to assess the prevalence, transmission patterns, risk factors, and potential interventions for Hepatitis B among children below the age of five. These studies should also assess the community’s knowledge and practices regarding Hepatitis B and immunization. Methods The cross- sectional study will include a sample size of 2700 children aged between 1 to 5 years of Mayurbhanj district, Odisha. The serum samples will be tested for Hepatitis B surface antigen (HBsAg) and Hepatitis B surface antibody (anti-HBs). A detailed questionnaire will be prepared after focus group discussions with caregivers and healthcare workers to describe their knowledge and practices regarding HBV disease, associated risk factor and immunization. Discussion The prospective sero-epidemiological study conducted within the community will assist in determining the prevalence of Hepatitis B within the vulnerable population. It will provide valuable insights for monitoring the current status of Hepatitis B in Mayurbhanj district and contribute to enhancing ongoing efforts in vaccination, control, and eradication of Hepatitis B.